237 Evaluation of cooked and raw garbanzo beans as main plant protein sources in extruded feline diets. (5th December 2019) - Reilly, Lauren M; He, Fei; Mangian, Heather; Hoke, Jolene; Davenport, Gary; Godoy, Maria R C de
Abstract: Garbanzo beans (GB; Cicer arietinum) are a readily available pulse crop that have gained popularity as a plant-based protein source in the pet food industry. However, raw GB contain anti-nutritional factors that can reduce digestibility and cause effects in pets that are undesirable to owners. The objective of this study was to determine GB effects on digestibility, gastrointestinal tolerance, and fermentative end-products in cats fed extruded diets containing raw or cooked GB. Five diets were formulated to have either raw GB at 0%, 7.5%, 15%, or 30% or cooked GB at 30% inclusion. Ten, adult, male cats (mean age: 1.0 ± 0.0 years, mean BW: 4.7 ± 0.4 kg) were used in a replicated 5x5 Latin square design. Each period consisted of 14 d, with 10 d of diet adaptation followed by 4 d of total fecal and urine collection. At the end of each period, 4 mL of blood was collected and analyzed for a serum chemistry and complete blood count to ensure all animals remained healthy throughout the study. Cats were fed twice daily and food intake was calculated to maintain body weight. Food intake was highest (P < 0.05) for cats fed 0% raw GB (72.2 g/d, DMB) compared to higher GB inclusions (average 70.3 g/d, DMB). Dry matter and organic matter apparent total tract digestibility (ATTD) were lowest (P < 0.05) among all treatments for the cats consuming the 30% cooked GB diet (77.3% and 81.7%, respectively). Cats fed 7.5% raw GB had higher (P < 0.05) crude protein ATTD (86.2%) than cats fed 15% raw GB (82.3%) or 30% cooked GB (81.6%). In conclusion, all inclusion levels of raw GB showed high digestibility (average >80%) and ideal fecal scores (average 2.9) demonstrating their adequacy as the primary protein source in feline diets up to 30% inclusion levels.